2018
DOI: 10.14202/vetworld.2018.1479-1485
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional potentialities of some tree leaves based on polyphenols and rumen in vitro gas production

Abstract: Aim:The study was conducted to evaluate eight tree leaves based on polyphenolic content and rumen in vitro incubation and gas production technique (RIVIGPT) for their nutritive potentiality.Materials and Methods:Eight selected tree leaves, namely Sesbania grandiflora, Melia dubia, Dillenia spp., Artocarpus heterophyllus, Commiphora caudata, Moringa oleifera, Leucaena leucocephala, and Acacia auriculiformis, were selected for proximate composition, forage fiber fractions, total phenolics (TPs), non-tannin pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Acacia trees have high rates of leaf-litter accumulation that is deposited in large quantities, which become waste and proliferate pests and diseases over time (Eyles et al ., 2008). These leaves could be beneficial for improving the production and quality of animal-sourced foods as they contain moderate contents of crude protein (CP, 130–175 g/kg DM; Salem, 2005), high contents of neutral detergent fibre (NDF, 180–457 g/kg; De Neergaard et al ., 2005; Giridhar et al ., 2018) and proanthocyanidins (up to 150 g/kg DM; Degen et al ., 2000; Xiong et al ., 2016) that have nutritional, helminth suppressant, anti-bloat, antioxidant and antimicrobial properties (Sottie et al ., 2014; Yoshihara et al ., 2014; Koenig et al ., 2018; Lima et al ., 2019). In this regard, the valorisation of Acacia leaves presents an economic incentive for the sustainable management of IAPs and opportunities to unlock new value chains for the Acacia and animal feed industries to progress towards a circular bioeconomy.…”
Section: Introductionmentioning
confidence: 99%
“…Acacia trees have high rates of leaf-litter accumulation that is deposited in large quantities, which become waste and proliferate pests and diseases over time (Eyles et al ., 2008). These leaves could be beneficial for improving the production and quality of animal-sourced foods as they contain moderate contents of crude protein (CP, 130–175 g/kg DM; Salem, 2005), high contents of neutral detergent fibre (NDF, 180–457 g/kg; De Neergaard et al ., 2005; Giridhar et al ., 2018) and proanthocyanidins (up to 150 g/kg DM; Degen et al ., 2000; Xiong et al ., 2016) that have nutritional, helminth suppressant, anti-bloat, antioxidant and antimicrobial properties (Sottie et al ., 2014; Yoshihara et al ., 2014; Koenig et al ., 2018; Lima et al ., 2019). In this regard, the valorisation of Acacia leaves presents an economic incentive for the sustainable management of IAPs and opportunities to unlock new value chains for the Acacia and animal feed industries to progress towards a circular bioeconomy.…”
Section: Introductionmentioning
confidence: 99%
“…Its use in sheep feed (Jibril et al, 2020) and its medicinal uses of the secondary metabolites (Shah, 2017) have been reported. The content of total phenolics and condensed tannins in forages can improve nutrient utilisation due to their antibacterial and antifungal properties as previously reported in some mistletoe species such as A. oxycedri and A. americanum (Zaidi et al, 2006;Pernitsky et al, 2011;PKB, 2021a, 20021b), furthermore condensed tannins possess the ability to bind proteins that promote the passage of protein into the duodenum where it is absorbed (Giridhar et al, 2018;Lagrange et al, 2021;Menci et al, 2021), inhibit the secretion of microbial enzymes that digest the cell wall of forages (Zhang et al, 2021) and thereby modify the total digestibility of the ration (Vázquez-Carrillo et al, 2020;Huang et al, 2021). The addition of condensed tannins to ruminant diets provides some environmental benefits by reducing ammonia emissions (Menci et al, 2021).…”
Section: Introductionmentioning
confidence: 60%
“…In addition, the highest CP content was obtained from SBT, TIT, and WBU. In evaluating chemical composition and in vitro degradation of different edible trees, [19] observed that SBT (M. dubia) had 308 g/kg NDF and 165 g/kg CP content and 0.881 of in vitro dry matter degradation, which reinforces the high nutritional value of SBT. The high nutritional value of mulberry (BMU and WMU) leaves has been well documented [20,21].…”
Section: Discussionmentioning
confidence: 76%